The effectiveness of two arbuscular mycorrhiza species on growth of cocoa (Theobroma cacao L.) seedlings - Viva Rini, Maria; Hashim, Azizah; Zainal Abidin, Mohd Idris (Universiti Putra Malaysia Press, 1996)
A pot experiment was conducted to study the effectiveness of two arbuscular mycorrhiza (AM) species in enhancing growth of cocoa seedlings. Cocoa seedlings of hybrid UITI X Na32 inoculated with Glomus mosseae and Seutellospora ealospora either as a single inoculum or as a mixed inoculum and an uninoculated control were grown in 2 kg sterilized Tai Tak series soil. The experiment was a single factor experiment arranged in a completely randomized design, with type of inoculum as a factor with four replications. Of the four treatment used, plants inoculated with mixed inoculum Glomus mosseae and Seutellospora ealospora gave more pronounced and significant vegetative growth and higher percentage of root colonization than the other treatments. Maximum plant height and total leaf area of43.7 cm and 1819.2 cm2 respectively were obtained from seedlings inoculated with mixed inoculum compared to seedlings given either G. mosseae (37.9 cm dan 1007.2 cm2 ) , or S. ealospora (32.3 cm and 1316 cm2 ) and control (28.5 cm and 736.7 cm2 ). The highest percentage of root colonization (72%) was aslo recorded from seedlings inoculated with mixed inoculum followed by those given S. ealospora (54%) and single inoculum G. mosseae (43%).